Kebijakan Fiskal Dalam Perekonomian Islam Di Masa Khalifah Umar Bin Al-Khathab - Muhammad Fauzan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2017)
Umar bin Al-Khathab was one of the caliphs of the most successful in the history of Islam, it can be seen from the progress of the country and welfare of the people at the time he led both in terms of economic, social, political, security and defense of the country, and the development of science and technology, In terms of economic policy, especially fiscal policy, Umar bin Al-Khathab many uses diligences. This fact certainly raises the question: what the nature of fiscal policy in the future Caliph Umar bin Al-Khathab? To obtain the answer to that question, this study aimed at library research (library research) which is a descriptive analysis that describes the overall biography of Umar bin Al-Khathab and diligences 'Umar bin Al-Khathab in economic terms, especially in terms of fiscal policy. Data on policies Umar bin Al-Khathab in economic terms, especially in terms of fiscal policy be traced in the works of scholars, researchers and historians who wrote about Umar bin Al-Khathab. While the data related to this study traced in the sources of secondary and tertiary as well as previous studies. After a successful data are collected, grouped, categorized and discard unnecessary data and data obtained will be analyzed carefully. Based on the analysis of the data found that the policy (diligence) economy made by Umar bin Al-Khattab was the policy (diligence) that correspond/fit with the state of society at that time. Economic policies made by Umar bin Al-Khattab based on the Qur'an, the Hadith, or diligence Umar bin Al-Khattab or the friends at the time.